Perancangan Kursi Makan Lipat pada Ruang Makan Apartemen Minimalis - Meykel Ardy Samuel Elsa (Intra, 2017)
Apartment is a type of resident space, that only takes a small space from the building itself. Living in an apartment is the most favorable lifestyle and is currently on demand by the modern society, in addition to maximizing the use of reducing land as well as the use of facilities that can be obtained from apartment occupancy. The Square Apartment is the apartment that will become my design site because of its close distance to Petra Christian University and high number of students who choose to live in The Square Apartments, the user data used is a students who have an apartment with a minimalist type, furniture that will be placed in the minimalist room will greatly affect the owner’s activity, comfort, and the appearance of the room itself, apartments with a minimalist style is usually lack of circulation due to the amount of furniture that is too much or the size of appropriate furniture, the dining room is the most often experienced circulation disturbance area, Therefore it needs furniture that can be folded to be more effective and efficient, therefore I designed folding chair that can be used by one person, it can changed its shape to be used for two people, then can be used as casual table, and can be saved when not in use. This is the right solution and innovation to answer the existing problem.